Can combining triple‐arterial phase acquisition with fluoroscopic triggering provide both optimal early and late hepatic arterial phase images during gadoxetic acid‐enhanced MRI?. Issue 5 (15th October 2015) - Sofue, Keitaro; Marin, Daniele; Jaffe, Tracy A.; Nelson, Rendon C.; Bashir, Mustafa R.
Abstract : Purpose: To determine whether triple‐arterial phase acquisition with fluoroscopic triggering can provide both well‐timed early and late hepatic arterial phase (HAP) images more frequently than when using a fixed‐time delay during gadoxetic acid‐enhanced magnetic resonance imaging (MRI). Materials and Methods: Written informed consent was obtained for this Institutional Review Board (IRB)‐approved prospective, Health Insurance Portability and Accountability Act (HIPAA)‐compliant study. Ninety patients underwent gadoxetic acid‐enhanced MRI at 3T with a single‐breath‐hold triple‐arterial phase acquisition using either a fixed‐time delay ( n  = 45) or fluoroscopic triggering injection protocol ( n  = 45). Three radiologists, blinded to method of timing and other data, independently determined whether well‐timed early or late HAP were obtained for each arterial phase image set and assessed for transient severe motion (TSM). Rates of successful HAP acquisitions and of TSM were compared between the two protocols using χ 2 or Fisher's exact test. Results: The rate of successful acquisition of late HAP images was similar in the two groups (93% [42/45] for fixed‐time delay vs. 98% [44/45] for fluoroscopic triggering, P  = 0.62). There was a trend toward higher rates of successful acquisition of both early and late HAP images in the fluoroscopic triggering group (69% [31/45] vs. 49% [22/45], P  = 0.05). TSM occurred in five patients (6% [5/90]) and at similar frequencies in the two groups (2% [1/45] vs. 9% [4/45], P  = 0.36). Conclusion: Triple‐arterial phase acquisition with fluoroscopic triggering tended to provide both well‐timed early and late HAP images more frequently than when using a fixed‐time delay during gadoxetic acid‐enhanced MRI. J. Magn. Reson. Imaging 2016;43:1073–1081.